Environmental Factors and Management Strategies Influencing Sungkai (Peronema canescens Jack.) Population Dynamics in City Forest, West Wales, Universitas Indonesia Campus, Depok - Azmi Syafanah Nur Hasna; Yasman (Postgraduate, University of Mataram, 2024)
Sungkai (Peronema canescens), commonly used as an ornamental plant for household demarcation due to its aesthetic appeal, also offers medicinal benefits, effectively utilized in treating diverse ailments encompassing diseases, infections, and inflammations. This study aims to investigate the population dynamics and growth parameters of sungkai in the City Forest, West Wales, Universitas Indonesia Depok, we are focusing on various environmental factors and management practices affecting their development. Measurements of light intensity, temperature, humidity, soil pH, moisture, and wind speed were conducted to assess their impact on sungkai growth. The acquired data undergoes analysis through established formulas, and the outcomes are depicted in diagrams and tables. Results revealed congruence in altitude and light intensity with ideal growth conditions, while discrepancies in air humidity, soil pH, and moisture posed potential limitations to sungkai plant development. Analysis of sungkai tree diameters showcased varied growth rates, possibly influenced by plant spacing and nutrient competition. Furthermore, proposed intensive care practices such as pruning, thinning, and pest management are suggested as vital strategies to optimize sungkai growth. Overall, addressing these environmental factors and employing suitable management practices could significantly contribute to sustaining and enhancing the sungkai population within the City Forest, West Wales, Universitas Indonesia Depok.